Your customers' perception of quality : what it means to your bottom line and how to control it - Kureemun, Baboo; Fantina, Robert (CRC Press, 2011)
Providing the insight and tools needed to improve the perception your customers have about the quality of your product or service, Your Customers' Perception of Quality: What It Means to Your Bottom Line and How to Control It introduces a ground-breaking model for measuring the impact of quality perception on your bottom line. Allowing you to look at quality from an outside-in, truly customer-centric perspective, the authors pave a concrete connection between enhanced customer perception and increased profitability.